الغذاء الآمن في منهاج النبوة والعصر الحديث: (دراسة وصفية تحليلية) - Elhned, Ahlam Mohammad (Tobruk University Journal of Social and Human Sciences, 2024)
Praise be to God, and prayers and peace be upon the Messenger of God, may God’s prayers and peace be upon him, and I bear witness that there is no god but God and that Muhammad is His servant and Messenger The Sunnah of the Prophet guided the importance of food for the human body and showed the most important foods that raise his physical capabilities, keep him away from diseases and illnesses, and enhance his natural immunity. The modern era is a descriptive analytical study. The research was based on an introduction and three topics, the introduction included the importance of the research, its objectives, and methodology and research plan. The first topic came to study the method of prophecy in food, and it includes the definition of food, the types of prophetic food, and the method of prophecy in eating food. The second topic concerned the study of the method of prophecy in preserving food from contamination, the third topic dealt with food in the modern era, and it mentions the types of additives, diseases and damages that these additions may cause.